Difference in mechanical properties between plastic and metal molds for injection molding a talc reinforced rubber modified polypropylene. Issue 10 (5th September 2022) - Zhang, Dan; Bartlett, Leah; Cai, Kaiyu; Hoffman, Ben; Mulyana, Rachmat; Herderick, Edward; Castro, Jose M.
Abstract: Tooling for injection molding is costly, and delivery time is a concern, especially for companies that are on a tight production schedule. The introduction of additive manufacturing tooling for injection molding is an attractive rapid tooling for cutting cost and time not only for prototype parts but also for low volume production, that is, less than 100 parts. In this work, digital acrylonitrile butadiene styrene (ABS) mold insert was 3D printed on a Stratasys PolyJet printer, and then installed on the mold frame for injection molding investigation. The mechanical properties of talc reinforced rubber modified polypropylene (PP) parts molded by 3D printed ABS mold and conventional steel mold are compared. When the 3D printed ABS mold was used, a significantly higher mold temperature was observed during the molding cycles compared to the steel mold because of the lower thermal conductivity of ABS. The ductility of PP parts molded by the ABS mold is much lower compared to the metal mold, while other mechanical properties, such as tensile strength, Young's modulus, and flexural strength are not significantly different. Abstract : Plastic mold versus steel mold plot shows lower cost, shorter lead time, and thus higher design flexibility. Molded parts depict slightly higher strength and much lower ductility that can be improved.